Blood moon eaudiobook A strange moon novella. - Graves, Jillian (Tantor Media, 2024)
Hazel knows exactly how to get over her bar's troubles: getting under something big, hairy, and monstrous at her coven's supernatural mixer. The hottest club in Los Angeles may be luring away her clientele, but for just one night she is ditching her responsibilities and indulging her fantasies. But the relief the witch seeks looks nothing like what she expects. Fur-free and bearing fangs, Vlad is more than an anonymous one-night stand. He's the mind-reading vampire whose every success brings Hazel's bar one step closer to ruin. After a century away from LA, Vlad has opened a club for humans and supernaturals alike. But a hot hookup brings him face-to-mind with the curvy witch who stands between him and his dreams. Understanding her desires as well as her heartfelt ambitions means navigating a passion studded with pitfalls. Will mixing business and pleasure brew a delicious new future together, or leave them with one hell of a supernatural hangover? Contains mature themes.